Colloidal quantum dots for thermal infrared sensing and imaging - Shihab Bin Hafiz (Nano Convergence, 2019)
Abstract Colloidal quantum dots provide a powerful materials platform to engineer optoelectronics devices, opening up new opportunities in the thermal infrared spectral regions where no other solution-processed material options exist. This mini-review collates recent research reports that push the technological envelope of colloidal quantum dot-based photodetectors toward mid- and long-wavelength infrared. We survey the synthesis and characterization of various thermal infrared colloidal quantum dots reported to date, discuss the basic theory of device operation, review the fabrication and measurement of photodetectors, and conclude with the future prospect of this emerging technology.